The suicide plan [videorecording (DVD)] - Navasky, Miri; Navasky, Miri; Navasky, Miri; O'Connor, Karen (Film editor); O'Connor, Karen (Film editor); O'Connor, Karen (Film editor); Lyman, Will, 1948- (PBS, 2013)
Examines the predicament shared by the terminally ill living in the United States: with the exception of Washington and Oregon, where assisted suicide is legal, an individual must seek help secretly from friends, family members, and activist organizations to put an end to their suffering.